"Let Them Eat Cake": Drought, Peasant Uprisings, and Demand for Institutional Change in the French Revolution - Maria Waldinger (Center for Economic Studies and ifo Institute (CESifo), 2023)
The paper studies whether a drought in 1788 affected the outbreak of peasant revolts during the French Revolution. I construct a community-level data set with information on local drought severity and peasant uprisings in 1789. Results indicate that those more affected by the drought more often participated in peasant revolts against the feudal system. Then, I investigate a mechanism through which drought may have affected peasant revolts. I find that those more affected by the drought had higher demand for institutional change as expressed in the lists of grievances. The results provide evidence on specific ways in which the drought of 1788 impacted the French Revolution, a milestone in the democratization of Western Europe.
Keywords: C91; D83; D91; D01; 330; cooperation; incentives; signalling; crowding out; experiment